2021
DOI: 10.3390/polym13223926
|View full text |Cite
|
Sign up to set email alerts
|

Delamination Behaviour of Embedded Polymeric Sensor and Actuator Carrier Layers in Epoxy Based CFRP Laminates—A Study of Energy Release Rates

Abstract: Fiber reinforced composites combine low density with high specific mechanical properties and thus became indispensable for today’s lightweight applications. In particular, carbon fibre reinforced plastic (CFRP) is broadly used for aerospace components. However, damage and failure behaviour, especially for complex fibre reinforcement set-ups and under impact loading conditions, are still not fully understood yet. Therefore, relatively large margins of safety are currently used for designing high-performance mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…This test confirms the discussion about the manufacturing and application of the sensing layer, and how to improve it, to achieve a robust sensing system. An approach for robust manufacturing process is given in [38], [39]. Results confirm the validity of the proposed localisation technique.…”
Section: Pre Impactmentioning
confidence: 71%
“…This test confirms the discussion about the manufacturing and application of the sensing layer, and how to improve it, to achieve a robust sensing system. An approach for robust manufacturing process is given in [38], [39]. Results confirm the validity of the proposed localisation technique.…”
Section: Pre Impactmentioning
confidence: 71%
“…This is performed in an 'off-the-shelf' manner for a seamless integration into the standard industrial series production process. It will be shown that the proposed concept is capable of withstanding the manufacturing conditions in terms of handling, positioning accuracy and processing temperature and results in full sensing/actuation functionality with a negligible impact on the structural performance in terms of interlaminar properties at the same time [11].…”
Section: Design and Manufacturing Of Temsal And Cfrp Demonstrator Str...mentioning
confidence: 99%
“…However, approaches on the integration of large insulation layers and their impact on the composite properties of CFRPs are only marginally described in literature [5,[7][8][9][10]. Recently, the influence of embedded polymeric layers on the interlaminar behaviour of CFRP composites has been investigated in detail in [11]. It has been shown that a combined PI-PO configuration could be particularly effective as a carrier material for electric components, due to its negligible impact on the interlaminar properties and electric insulation capabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these polymer materials, polyimide (PI) film materials have outstanding properties [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]: low density, high mechanical properties, great thermal stability, radiation resistance, corrosion resistance, excellent dielectric properties, and so on. Therefore, PI films can be used in microelectronics, aerospace, and other fields [ 9 , 10 , 11 , 12 ]. However, the coefficient of thermal expansion (CTE) of polyimide is much higher than that of inorganic materials such as metals and ceramics.…”
Section: Introductionmentioning
confidence: 99%